OPTIMALISASI MEDIA VIRTUAL PADA PRAKTIKUM IPA DENGAN KONSEP SISTEM PENCERNAAN MAKANAN PADA MANUSIA TERHADAP HASIL BELAJAR SISWA KELAS V SDN 02 CINTANAGARA - Asy’ari, Lutfi; Latifah, Hani (Bale Aksara, 2021)
The research was conducted at SDN 02 Cintangara, from the research data by giving treatment to one class, namely class V. Based on the results of the analysis and overall discussion of the research data regarding the optimization of the use of virtual media in science practicum on student learning outcomes, according to the problem formulation the researcher obtained a conclusion, namely the posttest results of students after using the virtual media for science practicum as many as 17 students with a complete score of an average of 85% above the KKM of all 20 students. Therefore, the t test calculation results obtained, obtained tcount = 4.377 ≥ t table = 1.734. Because tcount = 4.377 ≥ t table = 1.734 so that tcount is outside the receiving area Ho, then Ha is accepted and Ho is rejected. So it can be concluded in this study that there are optimal and significant learning outcomes in science subjects using practicum virtual media.